H+-conducting aromatic multiblock copolymer and blend membranes and their application in pem electrolysis - Bender, Johannes; Mayerhöfer, Britta; Trinke, Patrick; Bensmann, Boris; Hanke-Rauschenbach, Richard; Krajinovic, Katica; Thiele, Simon; Kerres, Jochen (Polymers, 2021)
As an alternative to common perfluorosulfonic acid-based polyelectrolytes, we present the synthesis and characterization of proton exchange membranes based on two different concepts: (i) Covalently bound multiblock-co-ionomers with a nanophase-separated structure exhibit tunable properties depending on hydrophilic and hydrophobic components’ ratios. Here, the blocks were synthesized individually via step-growth polycondensation from either partially fluorinated or sulfonated aromatic monomers. (ii) Ionically crosslinked blend membranes of partially fluorinated polybenzimidazole and pyridine side-chain-modified polysulfones combine the hydrophilic component’s high proton conductivities with high mechanical stability established by the hydrophobic components. In addition to the polymer synthesis, membrane preparation, and thorough characterization of the obtained materials, hydrogen permeability is determined using linear sweep voltammetry. Furthermore, initial in situ tests in a PEM electrolysis cell show promising cell performance, which can be increased by optimizing electrodes with regard to binders for the respective membrane material.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Acid–base blend membranes; Electrolyzer; Hydrogen crossover; MEA; Multiblock-co-ionomers; Partially fluorinated and sulfonated poly(arylene)s; PEM